Analysis of the Influence of Financial Literacy on Investment Decisions Mediated by Financial Behavior: A Study on Students of the Faculty of Economics and Business, Jenderal Achmad Yani University - Simatupang, Frido Sarita; Nugraha, Nugraha; Purnamasari, Imas (Research Collaboration Community (Rescollacom), 2024)
Investment is the activity of saving current funds to obtain future profits with the aim of getting value for money that can compete with the prevailing inflation rate. Lack of understanding or knowledge regarding how to invest, high risks and very limited income have resulted in the reluctance of Indonesian people to invest. The aim of this research is to obtain empirical evidence regarding the influence of financial literacy on investment decisions mediated by financial behavior among students at the Faculty of Economics and Business, Jenderal Achmad Yani University. The variables in this research are (1) financial literacy, (2) financial behavior, and (3) investment decisions. The research method used is descriptive verification and the approach used is quantitative. The population of this research is active students majoring in management and accounting at Jenderal Achmad Yani University. The sampling technique used was purposive sampling. The data collection technique is carried out by distributing online questionnaires (g-form). The data analysis techniques used in this research are simple linear regression analysis, multiple linear regression analysis, and the Sobel test. The research results show that financial literacy has a positive and significant influence on investment decisions, financial literacy has no influence on financial behavior, financial behavior has no influence on investment decisions, and financial behavior does not mediate the influence of financial literacy on investment decisions